Is twice better than once?—challenges of troponin measurements for risk prediction in the general population - Jansen, Henning; Rothenbacher, Dietrich; Koenig, Wolfgang (Annals of Translational Medicine; Vol 7, Supplement 6 (September 20, 2019): Annals of Translational Medicine, 2019)
Troponins and especially high-sensitive troponins (hs-cTn) have become a crucial part in every day clinical practice for more than 15 years to reliably diagnose myocardial infarctions and guide further therapeutic interventions in the acute setting (1). In addition to the predictive value, hs-cTn not only support the clinician while dealing with an acute coronary syndrome (ACS) but also help to identify individuals at risk for future cardiovascular events. Such prognostic value has been established in the general population (2) and also in patients with known coronary heart disease (CHD) (3).